Utilization of Palm Oil Fuel Ash in Brick Manufacturing for Lightweight Fired Clay Brick Production - Abdul Kadir, Aeslina; Sarani, Noor Amira (International Journal of Sustainable Construction Engineering and Technology, 2020)
The utilization of palm oil fuel ash (POFA) into fired clay bricks is one of the alternatives for minimizing disposal of POFA waste in landfill. This study was conducted to investigate the effects of different percentages of POFA waste (0, 1, 5, 10, 20 and 30%) incorporated into fired clay bricks. The manufactured bricks were fired at 1050Â°C with heating rate of 1Â°C/min. The formulation of 20 and 30% of POFA brick (POFAB) was prepared as a comparative purpose. The manufactured bricks were tested in terms of chemical composition, geotechnical properties and physical mechanical properties of brick. The results showed that replacement 5% of POFA into fired clay bricks could yield lightweight fired clay brick due to the formation of porosity inside the brick, thereby reducing dry density of bricks. However, the replacement more than 10% of POFA resulted in a weak bonding between brick particles. In terms of compressive strength, the incorporation of 1 to 5% of POFA was found to be useful for non-loading applications. To conclude, POFA can potentially be utilized in the production of fired clay bricks to produce low-cost, lightweight and environmentally friendly building materials.